Game on - Allen, Navessa (Allen, Navessa. Into darkness trilogy, 2026)
Book three in the #1 New York Times bestselling Into Darkness Series, following the dark rom-com sensations Lights Out and Caught Up . The game is on for these enemies-to-lovers with laugh-out-loud banter and scorching-hot brat play. I hate that woman. Tyler Neumann has spent years looking for his father, and not because he wants to meet the man. No, he wants to destroy him. And he'll manipulate whoever he can to exact his revenge. Including Stella McCormick. She's everything Tyler hates. Her wealth and privilege have protected her for her entire life, and Tyler thinks it's time she finally paid the price. Whether she's ready to or not. I hate that man. Stella might not believe in love at first sight, but loathing at first sight: no question. From the moment she sets eyes on Tyler in her tattoo parlor, she knows he's the devil planning to make her life hell. Forced to play the part of his girlfriend and invite him into her family's glittering circles, Stella quickly clocks Tyler's ulterior motives. But love and hate are two sides of the same coin, and soon she doesn't know which is worse: being blackmailed by a man who wants to ruin her, or that they can't seem to keep their hands off each other. This is an enemies-to-lovers dark romance with morally grey characters. Some themes and scenes may be disturbing to readers. Please check the content warning at the beginning of the book. Tropes: Enemies-to-lovers / Forced proximity / Fake dating / Rom-com / Morally grey MMC / Black cat FMC /Blackmail / Kidnapping / Power imbalance / Age gap / Betrayal and redemption / Dark past / Revenge.